Biogenesis and Biological Functions of Extracellular Vesicles in Cellular and Organismal Communication With Microbes - Fang, Yuan; Wang, Zhiwen; Liu, Xili; Tyler, Brett M. (Frontiers in Microbiology, 2022)
Extracellular vesicles (EVs) represent a prominent mechanism of transport and interaction between cells, especially microbes. Increasing evidence indicates that EVs play a key role in the physiological and pathological processes of pathogens and other symbionts. Recent research has focused on the specific functions of these vesicles during pathogen-host interactions, including trans-kingdom delivery of small RNAs, proteins and metabolites. Much current research on the function of EVs is focused on immunity and the interactions of microbes with human cells, while the roles of EVs during plant-microbe interactions have recently emerged in importance. In this review we summarize recent research on the biogenesis of these vesicles and their functions in biology and pathology. Many key questions remain unclear, including the full structural and functional diversity of EVs, the roles of EVs in communication among microbes within microbiomes, how specific cargoes are targeted to EVs, whether EVs are targeted to specific destinations, and the full scope of EV transport of virulence effectors and of RNA and DNA molecules.